Ovarian sclerosing stromal tumor - benign neoplasm of the young. A case study with literature review - Jakub Grzybowski; Patrycja Piętak; Konrad Merkisz; Sylwia Nemeczek; Agnieszka Marciniak; Klaudia Walczak; Karolina Jaskuła; Władysław Orłowski; Sylwia Zdun; Natalia Grzywna; Patrycja Walczak (Kazimierz Wielki University, 2023)
Sclerosing stromal tumor (SST), located in the ovary, is a very rare disease entity. To date, only a few hundred cases of ovarian SST have been confirmed worldwide. Preoperative diagnosis of stromal tumor is difficult, as clinically and radiologically it resembles other types of ovarian tumors. These tumors present nonspecific symptoms, with irregular menstrual bleeding, lower abdominal pain and palpable pelvic lesions being the most common. Differentiation and diagnosis is possible only thorough histopathological examination and immunophenotyping. In the present study, we presented a case report of a young, 20-year-old patient with an oligosymptomatic  ovarian stromal tumor. We compared and summarized the diagnostic and therapeutic process, as well as the tumor immunophenotypes, with recent cases reported in the literature.